A SOLUTION TO SYSTEM ACCESS PROBLEM BASED ON CONVOLUTIONAL NEURAL NETWORK APPROACH - N. A. Iskra (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The algorithm based on the principal components of the images as informative features extracting and convolutional neural network as a classifier is proposed. Experiments have shown partial invariance to the rotation, scaling and deformation, achieved through a hierarchical extraction of informative features. The resulting percentage of correct recognition rate of persons is up to 99%.